Anti‐thymocyte globulin and post‐transplant cyclophosphamide predisposes to inferior outcome when using cryopreserved stem cell grafts. (17th October 2021) - Novitzky‐Basso, Igor; Remberger, Mats; Chen, Carol; Pasić, Ivan; Lam, Wilson; Law, Arjun; Gerbitz, Armin; Viswabandya, Auro; Lipton, Jeffrey H.; Kim, Dennis D.; Kumar, Rajat; Mattsson, Jonas; et al.
Abstract: During 2020, the concurrent novel COVID‐19 pandemic lead to widespread cryopreservation of allogeneic hematopoietic cell transplant grafts based on National Marrow Donor Program and European Society of Blood and Marrow Transplantation recommendations, in order to secure grafts before the start of conditioning chemotherapy. We sought to examine the impact of this change in practice on patient outcomes. We analyzed the outcomes of 483 patients who received hematopoietic stem cell transplantation (HSCT) between August 2017 and August 2020, at Princess Margaret Cancer Centre, Canada, in the retrospective study, comparing the outcomes between those who received cryopreserved or fresh peripheral blood stem cell grafts. Overall compared with those who received fresh grafts (n = 348), patients who received cryopreserved grafts (n = 135) had reduced survival and GRFS, reduced incidence of chronic graft‐versus‐host disease (GvHD), delay in neutrophil engraftment, and higher graft failure (GF), with no significant difference in relapse incidence or acute GvHD. However, recipients of cryopreserved matched‐related donor HSCT showed significantly worse OS, NRM, GRFS compared with fresh grafts. Multivariable analysis of the entire cohort showed significant impact of cryopreservation on OS, relapse, cGvHD, GF, and GRFS. We conclude that cryopreservation was associated with inferior outcomes post‐HSCT, possibly due to the combination of ATG and post‐transplant cyclophosphamide impacting differential tolerance to cryopreservation on components of the stem cell graft; further studies are warranted to elucidate mechanisms for this observation.